“Un mapa de cicatrices microscópicas”. Vergüenza, dolor y resiliencia en la narrativa de Margarita García Robayo y de Bibiana Collado Cabrera - Gutkowska-Ociepa, Katarzyna (Studia Romanica Posnaniensia, 2026)
This article analyses two works by Margarita García Robayo – Primera persona (2019), El afuera (2024) – and Yeguas exhaustas (2023) by Bibiana Collado Cabrera, focusing on the representation of three kinds of experiences: shame, trauma, and female resilience. Through a hybrid narrative between fiction and essay, both authors explore the external mechanisms of female self-consciousness’ domination, linking them to social contexts such as cultural uprooting or societal expectations regarding motherhood. The authors reside in different regions of Latin American and Spain, addressing tensions between Colombian social imaginary and its Argentinian counterpart (García Robayo), as well as the interplay between provincial and metropolitan facets of personal identity (Collado Cabrera). Drawing on the affective turn (Sara Ahmed), the notion of intersectionality and various approaches to narrative heterogeneity (‘authorial text’, ‘self-essay’ or ‘critical fiction’), the article examines how testimonial and fictional components intertwine to express systemic and personal wounds.